2021
DOI: 10.1101/2021.07.06.21259982
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early initiation of corticosteroids in patients hospitalized with COVID-19 not requiring intensive respiratory support: cohort study

Abstract: ObjectivesTo determine whether early oral or parenteral corticosteroids compared to no corticosteroids are associated with decreased mortality in patients hospitalized with coronavirus disease 2019 (COVID-19) who are not on intensive respiratory support (IRS) within 48 hours of admission.DesignObservational cohort studySettingNationwide cohort of patients receiving care in the Department of Veterans Affairs, a large integrated US national healthcare systemParticipants9,058 patients admitted to a Veterans Affai… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Despite the proven efficacy of dexamethasone in lowering mortality predominantly in severe or critical COVID-19 patients, a large observational cohort study has demonstrated that dexamethasone treatment had no mortality benefit on those receiving supplemental oxygen via low-flow nasal cannula in the first 48 hours, while it increased mortality in patients not receiving oxygen (13). Moreover, dexamethasone has treatment-related adverse events, including hyperglycemia, cardiovascular events, and bacterial superinfections (83,84).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the proven efficacy of dexamethasone in lowering mortality predominantly in severe or critical COVID-19 patients, a large observational cohort study has demonstrated that dexamethasone treatment had no mortality benefit on those receiving supplemental oxygen via low-flow nasal cannula in the first 48 hours, while it increased mortality in patients not receiving oxygen (13). Moreover, dexamethasone has treatment-related adverse events, including hyperglycemia, cardiovascular events, and bacterial superinfections (83,84).…”
Section: Discussionmentioning
confidence: 99%
“…The greatest benefit was shown for patients receiving invasive mechanical ventilation compared to those on non-invasive oxygen support. A metaanalysis of the RECOVERY trial and subsequent studies support the beneficial effect on survival and ventilator-free days in patients with severe disease (12), but suggest that dexamethasone treatment in patients without oxygen support may be harmful (13).…”
Section: Introductionmentioning
confidence: 99%
“…The results of several randomized trials support the protective effect of systemic corticosteroid therapy in hospitalized patients with COVID-19 that require supplemental oxygen (Sterne et al, 2020;Li et al, 2021). In contrast, corticosteroids have shown no benefits and may harm hospitalized patients with milder COVID-19 who do not require supplemental oxygen (Horby et al, 2021;Crothers et al, 2022). Therefore, WHO guidelines recommend the use of corticosteroids for hospitalized patients with severe COVID-19 disease who are in need of oxygen supplementation (Corticosteroids for COVID-19 [internet], 2020).…”
Section: Sars-cov-2 In Cystic Fibrosis Patients An Intricate Interactionmentioning
confidence: 94%
“…Corticosteroids, as mentioned above, are the choice of medication by a standard medical practitioner to combat inflammation occurring in the lungs and other vital organs of patients infected with Coronavirus due to their potent anti-inflammatory properties (Li et al, 2021). Dexamethasone, a corticosteroid that has been previously shown to inhibit LPS-induced inflammation in both in vitro and in vivo models have been recommended for use in Corona patients also (RECOVERY Collaborative Group, 2021;Crothers et al, 2021). The unguided use of corticosteroids in patients, however, can be harmful in patients with metabolic diseases such as diabetes, hypertension, and other inflammatory diseases due to their side effects (Sterne and Murthy, 2020).…”
Section: Introductionmentioning
confidence: 99%